Tissue Surgery - Siemionow, Maria Z. (New Techniques in Surgery Series,, 2006)
Tissue Surgery details the most current and multidisciplinary approaches to new technologies used in general plastic, hand, peripheral nerve, microsurgery, breast, esthetic, and trauma surgery and provides an overview of the most important and clinically relevant plastic surgery research. Many of the techniques and procedures described have not been previously published in either textbooks or journals. New surgical images of new surgical approaches are all accompanied with anatomical descriptions. In a novel way, the book contains endoscopic images from minimally invasive procedures and provides the most current overview of the leading trends in plastic surgery research. Presenting newly developing clinically relevant techniques and technologies, this book stimulates the reader to look at future advances and applications of research and their relevance to daily clinical practice.